2019
DOI: 10.1016/j.celrep.2019.06.064
|View full text |Cite
|
Sign up to set email alerts
|

Coelomocytes Regulate Starvation-Induced Fat Catabolism and Lifespan Extension through the Lipase LIPL-5 in Caenorhabditis elegans

Abstract: Summary Dietary restriction is known to extend the lifespan and reduce fat stores in most species tested to date, but the molecular mechanisms linking these events remain unclear. Here, we found that bacterial deprivation of Caenorhabditis elegans leads to lifespan extension with concomitant mobilization of fat stores. We find that LIPL-5 expression is induced by starvation and that the LIPL-5 lipase is present in coelomocyte cells and regulates fat catabolism and longevity du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Compared with wild‐type animals, hlh ‐ 30 animals die prematurely during starvation (Harvald et al., 2017). Since mobilization of fatty acids from intestinal lipid stores is required for C. elegans to withstand long‐term starvation (Buis et al., 2019), we, therefore, hypothesized that exogenous supplementation of medium‐chain fatty acids, which cross the mitochondrial membranes independent of the carnitine‐shuttle system, would rescue the premature death of hlh ‐ 30 animals. We, therefore, examined survival under starvation conditions by transferring animals to empty plates supplemented with either a medium‐chain (lauric acid, C 12:0 ) or a long‐chain fatty acid (palmitic acid, C 16:0 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with wild‐type animals, hlh ‐ 30 animals die prematurely during starvation (Harvald et al., 2017). Since mobilization of fatty acids from intestinal lipid stores is required for C. elegans to withstand long‐term starvation (Buis et al., 2019), we, therefore, hypothesized that exogenous supplementation of medium‐chain fatty acids, which cross the mitochondrial membranes independent of the carnitine‐shuttle system, would rescue the premature death of hlh ‐ 30 animals. We, therefore, examined survival under starvation conditions by transferring animals to empty plates supplemented with either a medium‐chain (lauric acid, C 12:0 ) or a long‐chain fatty acid (palmitic acid, C 16:0 ).…”
Section: Resultsmentioning
confidence: 99%
“…The observation that fatty acid supplementation rescues lifespan of hlh ‐ 30 animals and extends longevity of wild‐type animals, suggests that mobilization of fatty acids from stored lipids is required for maintaining lifespan during starvation. Indeed, lipases like ATGL‐1, LIPL‐2, LIPL‐3, and LIPL‐5 are upregulated by dietary restriction and required for dietary restriction‐induced extension of lifespan (Buis et al., 2019; Lee et al., 2014; Murphy et al., 2019; Zaarur et al., 2019). Markedly, we recently found that loss of HLH‐30 diminishes expression of atgl ‐ 1 , lipl ‐ 2 , lipl ‐ 3 , and lipl ‐ 4 (Harvald et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, studies of C. elegans coelomocytes identified novel components of the endocytic machinery that are conserved in mammals (Fares and Greenwald, 2001 ; Sato et al, 2014 ). Moreover, C. elegans coelomocytes have been shown to regulate fat consumption and life span extension upon starvation (Buis et al, 2019 ). Finally, they participate in metal detoxification (Tang et al, 2020 ).…”
Section: Macrophage-like Cells In Acoelomate and Pseudocoelomate Protmentioning
confidence: 99%
“…Interestingly, a third of the annotated lipids, whose levels were changed, are triacylglycerols (TGs). TGs are storage lipids and make up a major part of lipid droplets, which are broken down into fatty acids and subsequently oxidized in mitochondria upon energy demand [82][83][84]. We initially determined the total amounts of TGs in the mutant backgrounds and compared them to that of wild type.…”
Section: Defects In Mitochondrial Dynamics Lead To Changes In the Levmentioning
confidence: 99%